SYSTEMATIC LITERATURE REVIEW: HUBUNGAN PENINGKATAN PEMBERIAN ASI EKSKLUSIF PADA IBU BEKERJA DENGAN PENDEKATAN HAPA (HEALTH ACTION PROCESS APPROACH) - Feralta, Sheeni; Murtiningsih, Murtiningsih (Seroja Husada: Jurnal Kesehatan Masyarakat, 2024)
Breast milk (breast milk) is the main and best food for babies that is incomparable. The benefits of exclusive breastfeeding are huge, especially for the baby's growth and development, immunity, psychology, and the economy of the baby's parents. Although the benefits of exclusive breastfeeding are obvious for mothers and their babies, the coverage of exclusive breastfeeding for babies is still low. The purpose of this study is to analyze the relationship between increasing exclusive breastfeeding in working mothers with the hapa (health action process approach). An example of this study is a working mother who has a baby 0-6 months in Batu Bara Regency. The sampling technique is Non-Probability Sampling using Total Sampling, where the number of samples is equal to a population of 100 people. The data processing method uses Univariate, Bivariate, and Multivariate tests. The results showed that self-efficacy, expectation of results, risk perception, planning, influence of intention, maintenance, and planning strategies to overcome obstacles had a significant effect on breastfeeding practices of working mothers in Batu Bara Regency as evidenced by the p-value of 0.000 <0.05 variables, respectively. The results of the multivariate test showed that together the independent variables had a significant influence on the dependent variables, with the most dominant variable being the maintenance variable with an average value of 10.66